International research collaboration : the way forward - Chotirmall, Sanjay Haresh (2019)
Academic respiratory medicine is entering a new and exciting era; one where diagnostic challenges are emerging, newer multi‐omic technologies are being increasingly applied and complex bioinformatic challenges involving artificial intelligence have arrived. The Singapore International Respiratory Consortium (SIRC) was formed in 2016 at a workshop convened at the National University of Singapore (NUS) to discuss and formalize collaborations that will address these challenges within the Asia‐Pacific region and globally. The second International Symposium on Respiratory Research was convened at the Lee Kong Chian School of Medicine, Nanyang Technological University (NTU), Singapore in March 2018 and included leaders in Respiratory Research from NTU, NUS, the University of Newcastle, Australia (UON), Karolinska Institutet (KI), Imperial College London (ICL), the University of British Columbia (UBC) and the University of Groningen (RUG). The consortium focused on three major themes and coincided with the formal launch of The Academic Respiratory Initiative for Pulmonary Health (TARIPH), a Singapore‐centric interdisciplinary respiratory research network.